THE RHETORIC OF THE "COLLECTIVE WEST" AND THE GLOBAL POLITICAL VIOLENCE - Stošić, Sanja (Serbian political thought, 2025)
This paper aims to critically examine the nature of political rhetoric formed in the era of post-democracy, that is, to point out the importance and role that political discourse has in the formation of political violence, understood primarily as a global postmodern phenomenon that in the broadest sense refers to the violent creation and imposition of certain policies, forms of behavior and cultural patterns. Relying on an analytical/interpretive approach, and in light of the war in Ukraine and the current geopolitical turmoil on the international political scene, this paper points not only to the correlation between political communication of a post-democratic society and political violence but also to the intensification and relativization of political violence within the framework of the neoliberal hegemonic concept of rule and the general tendency towards the de-sovereignization of states. Based on a qualitative interpretation of the Western political narrative inherent in the era of global escalation of violence, the main conclusion of the paper is the need to preserve a sovereign, i.e., politically responsible and organized state as a key factor of individual and collective security, as well as understanding the hybrid character of contemporary political conflicts.